Metabolite-sensing GPCRs controlling interactions between adipose tissue and inflammation - Duncan, Elaine M.; Vita, Luca; Dibnah, Bethany; Hudson, Brian D. (Frontiers in Endocrinology, 2023)
Metabolic disorders including obesity, diabetes and non-alcoholic steatohepatitis are a group of conditions characterised by chronic low-grade inflammation of metabolic tissues. There is now a growing appreciation that various metabolites released from adipose tissue serve as key signalling mediators, influencing this interaction with inflammation. G protein-coupled receptors (GPCRs) are the largest family of signal transduction proteins and most historically successful drug targets. The signalling pathways for several key adipose metabolites are mediated through GPCRs expressed both on the adipocytes themselves and on infiltrating macrophages. These include three main groups of GPCRs: the FFA4 receptor, which is activated by long chain free fatty acids; the HCA2 and HCA3 receptors, activate by hydroxy carboxylic acids; and the succinate receptor. Understanding the roles these metabolites and their receptors play in metabolic-immune interactions is critical to establishing how these GPCRs may be exploited for the treatment of metabolic disorders.